2017
DOI: 10.1007/s11419-017-0366-9
|View full text |Cite|
|
Sign up to set email alerts
|

The psychoactive drug 25B-NBOMe recapitulates rhabdomyolysis in zebrafish larvae

Abstract: N-Benzyl-substituted 2C class phenethylamines (NBOMes) are psychoactive designer drugs, with strong hallucinogenic and stimulant effects, even at low doses. The designer drug, 2-(4-bromo-2, 5-dimethoxyphenyl)-N-(2-methoxybenzyl) ethanamine (25B-NBOMe) is considered to be one of the most potent agonists of the serotonin-2A (5-HT2A) receptor. Recently, we reported the first lethal case of 25B-NBOMe intoxication with severe rhabdomyolysis, concluded by clinical, pathological and toxicological analyses. There are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In humans, it also includes mental status changes. In agreement with Kawahara et al (2017) the NBOMe compounds, which are serotonergic drugs, could induce effects associated with this syndrome caused mainly by excessive activation of serotonin receptors [ 4 ].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In humans, it also includes mental status changes. In agreement with Kawahara et al (2017) the NBOMe compounds, which are serotonergic drugs, could induce effects associated with this syndrome caused mainly by excessive activation of serotonin receptors [ 4 ].…”
Section: Discussionsupporting
confidence: 82%
“…Our data in zebrafish embryos exposed to 25C-NBOMe show an LC 50 value of 10.76 μg/mL. Studies with other NBOMe family members have shown a reduction in the survival rate of approximately 40 %, for the concentration of 0.5 μg/mL for 25B-NBOMe [ 4 ]. However, this exposure was only done starting at 4 dpf by Kawahara et al (2017).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations